Focus Group Discussion Terpimpin untuk Meningkatkan Kemampuan Kepala Sekolah dalam Menyusun Program Supervisi Akademik - Fauzi (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2023)
The problem in this supervisory action research is the low results of managerial supervision by school principals in carrying out their managerial duties as learning supervisors, both in terms of preparation of supervision programs, implementation of actions and in terms of follow-up supervision. In general, there are four stages in this action research, namely (1) planning, (2) implementation, (3) observation, and (4) reflection. The implementation of the actions in cycle 2 is very dependent on the results of the reflection in cycle 1 so that the goals set can be achieved. The formulation of the problem in this action research is how can the guided Focus Group Discussion (FGD) method increase the competency of elementary school principals in developing academic supervision programs. While the goal to be achieved is to find out the increase in the competence of the Head of SDN 01 Lingga in compiling a learning supervision program through guided Focus Group Discussion (FGD). The results of the study showed that there was an increase in the competence of the elementary school principal in carrying out academic supervision. This can be seen from the first cycle data obtained by a value of 36 or 64% (enough category) to 54 or 89% (very good category) in cycle II. Thus, the guided FGD was able to increase the competency of the head of SDN 01 Lingga in carrying out academic supervision.